1990
DOI: 10.2466/pr0.67.7.883-890
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Attitudes Towards Aids Precautions and Intention to Use Condoms

Abstract: This study investigated attitudes toward AIDS precautions of 370 15- and 16-yr.-old secondary school students. Attitudes reflected levels of apathy, denial, and confusion high enough to lead to concern for this potentially high-risk group. Intention to use condoms in future sexual encounters was related to sex, conflict and confusion about AIDS precautions, plus other attitudinal variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 10 publications
3
12
0
1
Order By: Relevance
“…Consistent with previous research (Baffi et al, 1989;Barling & Moore, 1990;Ishii-Kuntz et al, 1990), the findings of the current study indicated that attitudes toward condoms were related to actual condom use; participants who had used condoms had more positive attitudes toward them. It is important to note, however, that the causal link between attitudes and condom use is unknown.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous research (Baffi et al, 1989;Barling & Moore, 1990;Ishii-Kuntz et al, 1990), the findings of the current study indicated that attitudes toward condoms were related to actual condom use; participants who had used condoms had more positive attitudes toward them. It is important to note, however, that the causal link between attitudes and condom use is unknown.…”
Section: Discussionsupporting
confidence: 91%
“…Two particular sets of attitudes have received a great deal of attention: (a) attitudes toward condoms and (b) attitudes about AIDS. Generally speaking, people who have more positive attitudes toward condoms tend to have stronger intentions and are more likely to use condoms in the future (e.g., Baffi et al, 1989;Barling & Moore, 1990;Boyd & Wandersman, 1991;Ishii-Kuntz, Whitbeck, & Simons, 1990). Recent evidence suggests that concern about AIDS also is a significant predictor of intended (Ishii-Kuntz et al, 1990) and actual (Boyd & Wandersman, 1991) condom use.…”
mentioning
confidence: 93%
“…Richard and van der Pligt (1991) showed that knowledge about AIDS did not predict intentions, and Winslow, Franzini and Hwang (1992) also failed to find an influence of knowledge on unprotected casual sex and AIDS-preventive behaviours. Conversely, Krahe and Reiss (in press) showed a relationship between knowledge and the intention to use condoms among males and sexually inexperienced adolescents, and Barling and Moore (1990) between adolescents' knowledge about condoms and sexually transmitted diseases on one hand, and the intention to use condoms on the other hand.…”
mentioning
confidence: 99%
“…These behaviours potentially place heterosexual young people at risk of HIV infection. In addition, some young people appear to justify their non-use of condoms with the belief that they are unnecessary because their current relationship is monogamous and promises to be long term (Abbott, 1988;Barling & Moore, 1990;Crawford et al, 1990;Harlow et al, 1993;Kelly et al, 1989b;Kelly & Murphy, 1992;Moore & Rosenthal, 1991b;Perlman et al, Stall et al, 1986;Sunenblick, 1998).…”
Section: The Present Studymentioning
confidence: 95%